A push–pull thienoquinoidal chromophore for highly efficient p-type dye-sensitized solar cells1. Issue 15 (21st April 2015) - Zhang, Qian-Qian; Jiang, Ke-Jian; Huang, Jin-Hua; Zhao, Chuan-Wu; Zhang, Li-Peng; Cui, Xue-Ping; Su, Mei-Ju; Yang, Lian-Ming; Song, Yan-Lin; Zhou, Xue-Qin
<x xml:space="preserve">Abstract</x> A push–pull thienoquinoidal dye (QT-1), was synthesized as a sensitizer in a p-DSC, giving a high short-circuit photocurrent density of 8.2 mA cm−2. The result would pave new organic semiconductor sensitizers for use in p-DSCs and other organic optoelectronic devices.